2020
DOI: 10.1016/j.wroa.2020.100061
|View full text |Cite
|
Sign up to set email alerts
|

Predicting breakthrough of vanadium in fixed-bed absorbent columns with complex groundwater chemistries: A multi-component granular ferric hydroxide−vanadate−arsenate−phosphate−silicic acid system

Abstract: Granular ferric hydroxide (GFH) is often used for fixed bed adsorbent (FBA) columns in groundwater purification units around the world to remove arsenate contaminations. Groundwater can contain also other toxic (e.g., antimonite and vanadate) and non-toxic oxo-anions (phosphate and silicic acid) that are known to affect FBA lifetimes. Therefore, understanding the breakthrough of toxic compounds intended for removal by FBA is essential to their design, and is important to predict accurately breakthrough curves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…A mathematical model incorporating the HSDM has been applied to describe the concentration profiles of arsenic adsorption systems, 8,58–61 These studies have demonstrated that the HSDM allows the simulation of the dynamic behavior of a variety of adsorbates (phosphate, arsenic, chloroform and vanadium) onto porous adsorbents (e.g. activated carbon, GFH and μGFH), as long as the mass transfer from the solution to the adsorption sites within the adsorbent particles is constrained by mass transfer resistances such as surface diffusion and external film mass transfer, as depicted in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A mathematical model incorporating the HSDM has been applied to describe the concentration profiles of arsenic adsorption systems, 8,58–61 These studies have demonstrated that the HSDM allows the simulation of the dynamic behavior of a variety of adsorbates (phosphate, arsenic, chloroform and vanadium) onto porous adsorbents (e.g. activated carbon, GFH and μGFH), as long as the mass transfer from the solution to the adsorption sites within the adsorbent particles is constrained by mass transfer resistances such as surface diffusion and external film mass transfer, as depicted in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…It has been proven that the mathematical model based on the HSDM has the capacity to describe the impact of water chemistry (e.g. pH and water matrix) on adsorbate dynamic behavior if the adsorption equilibrium and kinetic parameters under changed water quality conditions are available (have been derived) 60,61 . This software (FAST 2.1) provides a numerical solution of Eqns (1) and (2) to simulate the concentration profile of anions over time of a fixed‐bed adsorption filter packed with an adsorbent used in water treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The effective surface diffusion coefficient gave distinct nonlinear intragranular adsorbate concentration gradients, as found by electron probe microanalysis of grains used to sorb vanadium. 14 Other assumptions incorporated into the HSDM approach were (i) that the hydraulic load rate and advective plug−flow conditions in the adsorbent bed (H in the HSDM) were constant, (ii) that solid phase mass transfer occurred through surface diffusion (SD in the HSDM), (iii) that linear aqueous phase mass transfer occurred through film diffusion, (iv) that the solute inflow concentrations were constant, (v) that the adsorbent grains were spherical, and (vi) that nonlinear (Freundlich or Langmuir) isotherms were used to describe the adsorption equilibrium. 17 The adsorbent bed used in the column experiments was characterized using bed length l, radius r, particle density ρ P , mean particle diameter d P , bed density ρ B , bed porosity ε B , adsorbent mass m A , and adsorbent bed volume BV.…”
Section: Adsorption Kinetics and Massmentioning
confidence: 99%
“…In early attempts, BTCs were fitted using Gompertz sigmoid functions, but the polynomial curves produced by these functions have no physical or chemical meaning and therefore cannot be used to investigate systematically the effects of key parameter interference on breakthrough, such as the effects of changes in the pH and phosphate, silicate, and arsenate co-adsorbate concentrations reported on vanadate breakthrough. 14 Key factors that affect U(VI) breakthrough have not yet been investigated in a systematic way. However, from our current understanding of U(VI) complexation chemistry in groundwater involving ternary Ca uranyl carbonato complexes, and the strong effects of these complexations on U(VI) adsorption by ferric hydroxides, we hypothesize that elevated carbonate oxyanion and Ca concentrations typical of mineral water can strongly affect U(VI) breakthrough in FBAs containing GFH adsorbents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation